Kebijakan Sosial sebagai Instrumen Keadilan bagi Anak Berkebutuhan Khusus: Studi Pusat Layanan Disabilitas Kota Blitar - Wydha Mustika Maharani (Universitas 17 Agustus 1945, 2025)
This study examines the role of the Disability Service Center (PLD) in Blitar City as a social policy instrument aimed at enhancing justice and access to services for Children with Special Needs (CSN). The main objective is to analyze the implementation of social policy through the integrated services provided by PLD, including diagnostic assessments, psychological therapy, occupational therapy, physiotherapy, speech therapy, and transition education, as well as to identify supporting and inhibiting factors. A qualitative descriptive approach was employed, utilizing in-depth interviews, participatory observations, and document studies for data collection. Findings reveal that PLD has successfully increased both the quantity and quality of services reaching various types of disabilities, supported by a multidisciplinary team of experts and adequate facilities. Active involvement of parents and teachers strengthens family empowerment and the sustainability of therapies. However, challenges such as social stigma, limited human resources, and funding constraints remain significant barriers. This study emphasizes that robust social policies and cross-sector collaboration are key to the success of inclusive services for CSN. Implications highlight the need to enhance human resource capacity, strengthen regulations, and broaden socialization efforts to optimize services and support social inclusion. Further research with quantitative methods and long-term impact evaluation is recommended.